2021
DOI: 10.1089/neur.2021.0021
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Pathology Evolves over Time in Rat Hippocampus after Lateral Fluid Percussion Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) causes acute and lasting impacts on the brain, driving pathology along anatomical, cellular, and behavioral dimensions. Rodent models offer an opportunity to study the temporal progression of disease from injury to recovery. Transcriptomic and epigenomic analysis were applied to evaluate gene expression in ipsilateral hippocampus at 1 and 14 days after sham ( n = 2 and 4, respectively per time point) and moderate lateral fluid percussion injury ( … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 79 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…and the up-regulation of pro-inflammatory genes (e.g., Nlrp3 and Tlr4) (Catta-Preta et al, 2021). Altogether, this suggests that changes in cholesterol metabolism after TBI may contribute to persistent neuroinflammation that can promote chronic neurodegeneration.…”
Section: Tb I D Is Rup Ts Mi Crog Lial Lipid Me Tabolis M and In Cre ...mentioning
confidence: 98%
See 1 more Smart Citation
“…and the up-regulation of pro-inflammatory genes (e.g., Nlrp3 and Tlr4) (Catta-Preta et al, 2021). Altogether, this suggests that changes in cholesterol metabolism after TBI may contribute to persistent neuroinflammation that can promote chronic neurodegeneration.…”
Section: Tb I D Is Rup Ts Mi Crog Lial Lipid Me Tabolis M and In Cre ...mentioning
confidence: 98%
“…In a diffuse injury model in rats (fluid percussion injury), ABCA1 was increased at 10 days post‐injury, but brain cholesterol levels did not correlate with liver pro‐inflammatory markers IL‐1α, IFNγ, TNFα, and MCP‐1 (Palafox‐Sanchez et al, 2021). At later time points, sterol biosynthesis genes were down‐regulated in injured tissue, and were accompanied by down‐regulation of microglial immunoregulatory genes (e.g., P2ry12 ) and the up‐regulation of pro‐inflammatory genes (e.g., Nlrp3 and Tlr4 ) (Catta‐Preta et al, 2021). Altogether, this suggests that changes in cholesterol metabolism after TBI may contribute to persistent neuroinflammation that can promote chronic neurodegeneration.…”
Section: Tbi Disrupts Microglial Lipid Metabolism and Increases Keton...mentioning
confidence: 99%
“…[79][80][81][82][83] While not many changes in gene expression were reported between days 14 and 30 after TBI, large numbers of genes appear to remain either up-or downregulated long-term. 79,81 In our study, we find that CCI induces persistent changes in gene expression patterns in Vehicle-CCI animals, with the majority of differentially expressed genes involved in inflammation and tissue repair (Figure 3). Conversely, we find that thymus extract supplementation and TNF supplementation, in particular, induce notably larger changes in hippocampal gene expression patterns compared to Vehicle-CCI group (797 vs. 70 differentially expressed genes for TNF-CCI versus Vehicle-CCI groups, respectively) (Table S1).…”
Section: Serum Igg Levels Correlate With Vestibulomotor Function Reco...mentioning
confidence: 99%
“…Multiple studies have reported dramatic changes in rat hippocampal gene expression levels following moderateto-severe TBI at both the early, acute timepoints after the injury and throughout the recovery period. [79][80][81][82][83] While not many changes in gene expression were reported between days 14 and 30 after TBI, large numbers of genes appear to remain either up-or downregulated long-term. 79,81 In our study, we find that CCI induces persistent changes in gene expression patterns in Vehicle-CCI animals, with the majority of differentially expressed genes involved in inflammation and tissue repair (Figure 3).…”
Section: Serum Igg Levels Correlate With Vestibulomotor Function Reco...mentioning
confidence: 99%
“…We downloaded two mRNA expression datasets (GSE111452 and GSE173975) from the GEO database (ht tps://www.ncbi.nlm.nih.gov/geo/) [18,19]. In two experiments, adult male Sprague-Dawley (SD) rats were used as the experimental models.…”
Section: Dataset Sourcementioning
confidence: 99%